Cultural significance of locusts, grasshoppers, and crickets in sub-Saharan Africa - Arnold van Huis (BMC, 2022)
Abstract Background In sub-Saharan Africa, there is a wealth of information about insects which is often only orally available. The purpose of the study was to remedy this shortcoming and make an overview of how orthopteran species are utilised, perceived and experienced in daily life across sub-Saharan Africa. Method Ethno-entomological information on Orthoptera in sub-Saharan Africa was collected by (1) interviews with more than 300 people from about 120 ethnic groups in 27 countries in the region; (2) library studies in Africa, London, Paris and Leiden; and (3) using web search engines. Results More than 126 species of crickets, grasshoppers, and locusts have been identified as edible in sub-Saharan Africa. Some toxic species, such as Zonocerus spp., are eaten by some groups who use processing and detoxifying techniques. The katydid Ruspolia differens is very popular as food in central and eastern Africa and is captured by indigenous and commercial methods. Vernacular names refer to their morphology, behaviour, characteristics or the beliefs associated with the insect. The aposematic pyrgomorphid species, such as Zonocerus spp., are often used as medicine. Children play with grasshoppers, by for instance herding them like cattle, and they consider cricket-hunting for food as a game. The doctrine of signatures probably plays a role, as crickets, because of their chirping, are used to improve the sound of a music instrument, or as medicine to treat earache. Locust plagues are considered a punishment which requires repentance, but also an opportunity to acquire food. Proverbs and stories relate to using the orthopterans as food or to the underground lives of the crickets. Possible explanations are given as to why so many practices, beliefs and stories about orthopterans are so widespread in sub-Saharan Africa. The relevance of recording such ethno-entomological practices is discussed. Conclusion Grasshoppers, locusts and crickets, although they may be agricultural pests, are very popular as food. They are also used in medicine, and as toys, and they play a role in religion, art and literature.